2022
DOI: 10.1155/2022/6217328
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Intelligent Archives Management Based on Data Mining in Hospital Archives Management

Abstract: Data mining belongs to knowledge discovery, which is the process of revealing implicit, unknown, and valuable information from a large amount of fuzzy application data. The potential information revealed by data mining can help decision makers adjust market strategies and reduce market risks. The information excavated must be real and not universally known, and it can be the discovery of a specific problem. Data mining algorithms mainly include the neural network method, decision tree method, genetic algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…It must also be able to synchronize electronic and conventional carrier archiving materials, issue file numbers automatically based on categorization findings, and finish the archiving process. It must be able to create and name folders automatically and level by level based on each component of the file number, categorize and store electronic files, and name electronic files with the file number [6]. e technical means provided by the third-party authority shall be used to generate the solidified information of the original text of the electronic archives at an appropriate time to provide verification channels.…”
Section: Experiments and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It must also be able to synchronize electronic and conventional carrier archiving materials, issue file numbers automatically based on categorization findings, and finish the archiving process. It must be able to create and name folders automatically and level by level based on each component of the file number, categorize and store electronic files, and name electronic files with the file number [6]. e technical means provided by the third-party authority shall be used to generate the solidified information of the original text of the electronic archives at an appropriate time to provide verification channels.…”
Section: Experiments and Analysismentioning
confidence: 99%
“…e digitized archives can use big data and cloud computing technology to reasonably calculate and adjust the actual demand, quickly match the relevant resources, provide rapid feedback, and e ectively solve the problem of a "bloated library" in traditional archives management. For the archives themselves, digitization will lead to a new era by utilizing the core of big data [5,6], which lies in mining value from the massive amount of data. First, digitization has completely changed the way archives are used and greatly improved the utilization rate of archives.…”
Section: Introductionmentioning
confidence: 99%
“…Management" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
Section: Journal Of Electrical and Computer Engineering Has Retracted...mentioning
confidence: 99%
“…Archive management is one of the archive processing activities carried out within the agency, (J. Li, 2022;Odhiambo, 2018). Archives must be arranged so that stored records can be easily found again when they are needed.…”
Section: Introductionmentioning
confidence: 99%